2003
DOI: 10.1080/0950069032000052207
|View full text |Cite
|
Sign up to set email alerts
|

Skill and will: The role of motivation and cognition in the learning of college chemistry

Abstract: This study investigated how students' level of motivation and use of specific cognitive and self-regulatory strategies changed over time, and how these motivational and cognitive components in turn predicted students' course performance in chemistry. Participants were 458 students enrolled in introductory college chemistry classes. Participants' motivation and strategy use were assessed at three time points over the course of one semester using self-report instruments. Results showed an overall decline in stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

41
285
3
25

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 388 publications
(354 citation statements)
references
References 16 publications
41
285
3
25
Order By: Relevance
“…Specifically, researchers seem to agree that a mastery goal is related to "an adaptive pattern of attributions and positive affect that will help a student try hard, persisting, and ultimately doing better on academic tasks" (Pintrich & Schunk, 1996, p. 239). For instance, it has been documented that mastery oriented students process the learning information at a deep level (Ames & Archer, 1988;Pintrich, 2000b), that they are more cognitively engaged in a task (Pintrich & Schrauben, 1992), use more metacognitive and self-regulating strategies (Meece, Blumenfeld, & Hoyle, 1988), enjoy their learning more (Elliot & Church, 1997) and tend to obtain better academic grades (e.g., Botsas & Padeliadu, 2003;Vansteenkiste, Simons, Lens, Soenens, Matos, & Lacante, 2004, Zusho & Pintrich, 2003. It must be noted though that some researchers have failed to replicate the latter finding (e.g., Harackiewicz, Barron, & Elliot, 1998) and instead showed that performance approach goals were most predictive of academic achievement.…”
Section: Mastery and Performance Achievement Goalsmentioning
confidence: 99%
“…Specifically, researchers seem to agree that a mastery goal is related to "an adaptive pattern of attributions and positive affect that will help a student try hard, persisting, and ultimately doing better on academic tasks" (Pintrich & Schunk, 1996, p. 239). For instance, it has been documented that mastery oriented students process the learning information at a deep level (Ames & Archer, 1988;Pintrich, 2000b), that they are more cognitively engaged in a task (Pintrich & Schrauben, 1992), use more metacognitive and self-regulating strategies (Meece, Blumenfeld, & Hoyle, 1988), enjoy their learning more (Elliot & Church, 1997) and tend to obtain better academic grades (e.g., Botsas & Padeliadu, 2003;Vansteenkiste, Simons, Lens, Soenens, Matos, & Lacante, 2004, Zusho & Pintrich, 2003. It must be noted though that some researchers have failed to replicate the latter finding (e.g., Harackiewicz, Barron, & Elliot, 1998) and instead showed that performance approach goals were most predictive of academic achievement.…”
Section: Mastery and Performance Achievement Goalsmentioning
confidence: 99%
“…En tercer lugar, se examinó la relación de las puntuaciones con el rendimiento del alumno en los cursos universitarios de matemática realizados previamente y con el rendimiento general futuro en la universidad, medido tres años después. Dado que la bibliografía sugiere la existencia de efectos positivos de las metas de aprendizaje sobre el rendimiento de estudiantes universitarios de carreras científi cas (Grant & Dweck, 2003;Rhee, Zusho, & Pintrich, 2005;Rodrí-guez Ayán, 2007;Rodríguez Ayán & Ruiz, 2012;Zusho, Pintrich, & Coppola, 2003) extendemos tales hallazgos a la valoración de la matemática en su componente de interés, por considerar a esta dimensión equiparable a las metas de aprendizaje. Así, postulamos que la dimensión interés estará positivamente asociada al rendimiento.…”
unclassified
“…Son diversas las investigaciones que muestran cómo los enfoques de aprendizaje se relacionan con elementos básicos relativos a la competencia para el aprendizaje a lo largo de la vida (life long learning), como son: autorregulación (Suarez et al, 2004), buen auto-concepto académico (Gargallo, 2006), autoeficacia (Zusho et al, 2003) y motivación intrínseca (Gil et al, 2009;Rinaudo et al, 2003).…”
Section: Marco Teóricounclassified